2012
DOI: 10.1002/cbic.201100798
|View full text |Cite
|
Sign up to set email alerts
|

Establishing a New Methodology for Genome Mining and Biosynthesis of Polyketides and Peptides through Yeast Molecular Genetics

Abstract: Fungal genome sequencing has revealed many genes coding for biosynthetic enzymes, including polyketide synthases and nonribosomal peptide synthetases. However, characterizing these enzymes and identifying the compounds they synthesize remains a challenge, whether the genes are expressed in their original hosts or in more tractable heterologous hosts, such as yeast. Here, we developed a streamlined method for isolating biosynthetic genes from fungal sources and producing bioactive molecules in an engineered Sac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 33 publications
1
64
0
Order By: Relevance
“…A similar convergent evolution of bacterial and fungal type I PKSs has previously been observed in orsellinic acid biosynthesis. While the fungal orsellinic acid synthases are typical fungal nonreducing PKSs (41)(42)(43), the bacterial orsellinic acid synthases are related to bacterial iterative type I PKSs (homologous to fungal PR-PKSs) and are likely to have evolved from ancestral bacterial 6MSASs via mutations in the KR domain (44)(45)(46). From a protein engineering perspective, the convergent evolution of MLNSs implies that there is more than one way in nature to modify the chain length specificity and ketoreduction regioselectivity of iterative PKSs.…”
Section: Discussionmentioning
confidence: 99%
“…A similar convergent evolution of bacterial and fungal type I PKSs has previously been observed in orsellinic acid biosynthesis. While the fungal orsellinic acid synthases are typical fungal nonreducing PKSs (41)(42)(43), the bacterial orsellinic acid synthases are related to bacterial iterative type I PKSs (homologous to fungal PR-PKSs) and are likely to have evolved from ancestral bacterial 6MSASs via mutations in the KR domain (44)(45)(46). From a protein engineering perspective, the convergent evolution of MLNSs implies that there is more than one way in nature to modify the chain length specificity and ketoreduction regioselectivity of iterative PKSs.…”
Section: Discussionmentioning
confidence: 99%
“…This technique, which we termed "overlap-extension PCR-yeast homologous recombination (ExRec)," allowed reliable preparation of a S. cerevisiae expression plasmid containing the full-length, intron-free open reading frame of a target large fungal gene synthesized from a pool of total mRNA. 16) Next, the expression vector was introduced into an engineered S. cerevisiae strain SCKW5, whose genome is modified to include a G418 resistance marker kanMX, a malonyl-CoA synthetase gene matB and a phosphopantetheinyl transferase gene npgA. 16) Expression of the foreign gene was checked by Western blotting analysis, and biosynthesis of the corresponding nonribosomal peptide compound was examined.…”
Section: Engineered Biosynthesis Of Complex Natural Products In Hetermentioning
confidence: 99%
“…16) Next, the expression vector was introduced into an engineered S. cerevisiae strain SCKW5, whose genome is modified to include a G418 resistance marker kanMX, a malonyl-CoA synthetase gene matB and a phosphopantetheinyl transferase gene npgA. 16) Expression of the foreign gene was checked by Western blotting analysis, and biosynthesis of the corresponding nonribosomal peptide compound was examined. The culture of pKW5022 (Afu6g12080)/SCKW5 contained peptide products 37 (Chart 9A) and 49 (Chart 13) with approximate yields of 0.4 and 1.8 mg/L of culture, respectively.…”
Section: Engineered Biosynthesis Of Complex Natural Products In Hetermentioning
confidence: 99%
See 1 more Smart Citation
“…1). The PKSs include five from A. nidulans shown to produce orsellinic acid or derivatives (Ahuja et al, 2012), a PKS from Cladonia grayi hypothesized to be responsible for production of orsellinic acid in route to the synthesis of the orcinol depsidone grayanic acid (Armaleo et al, 2011), and a PKS from Coprinopsis cinerea shown in Saccharomyces cerevisiae to produce orsellinic acid (Ishiuchi et al, 2012). The resulting genealogy resolved the 32 PKSs into three major clades each with 100% bootstrap support.…”
Section: Phylogenetic Analyses Of Pks14mentioning
confidence: 99%